Culture, Personal Development, and Intercultural Differences (Comparative & International Education Series, 2022)
My story focuses on culture, personal development, and intercultural differences. In 2007, I went to study for my master’s degree in Psychology (Human Development) at the Norwegian University of Science and Technology (NTNU) as a beneficiary of the Norwegian Quota Scholarship Program. I decided to discuss two of my experiences during my time as an international master’s student in Norway.